A Systematic Literature Review: Characteristic of Ethnomathematical-Based Subject Specific Pedagogy - Nuryadi, Nuryadi; Zaenuri, Zaenuri; Kharisudin, Iqbal (Technium Social Sciences Journal, 2021)
Ethnomathematics-based Subject Specific Pedagogy (SSP) is a learning instrument packaged in a comprehensive, complete and systematic way for mathematics material in cultural studies. The era of society 5.0 is a human-centered and technology-based concept through a system that integrates virtual and physical spaces. The influence of globalization on the life of the nation and state has an impact on the erosion of cultural values. Ethnomathematics-based SSP has a very important role in growing and developing the competence of teachers and students based on cultural values. Several studies have been synthesized with previous researches to provide an overview of the effectiveness of Ethnomathematics-based SSP. To overcome this problem, the Systematic Literature Review has been carried out by documenting and reviewing all articles related to mathematics education in the period 2010 - 2020. The articles used in this study are 19 articles of nationally and internationally accredited journals accessed from Google Schoolar, Research Gate, SINTA, DOAJ, and Scopus. The results of a literature review of 19 research articles that study pedagogy, and ethnomathematics with components of syllabus, lesson plans, student teaching materials, Student Worksheets (LKPD), and effective assessments in learning mathematics. It can be seen from several studies which show that by developing the SSP with cultural elements, it is able to grow students’ character and cultural insight. The application of an ethnomathematics-based learning model or approach to mathematics can improve problem solving and critical thinking skills. Meanwhile, ethnomathematics-based learning instrument can improve mathematical literacy